2016
DOI: 10.20344/amp.6889
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Mental State Examination: Avaliação dos Novos Dados Normativos no Rastreio e Diagnóstico do Défice Cognitivo

Abstract: RESUMOIntrodução: O Mini-Mental State Examination é o teste de rastreio de défice cognitivo/demência mais difundido. No nosso país têm-se utilizado pontuações de corte definidas por grupos de literacia, mas existem novas propostas sustentadas por estudos mais representativos. Propomo-nos confirmar a influência da idade e da escolaridade no desempenho, avaliar a capacidade discriminativa dos novos dados normativos e testar a acuidade diagnóstica das pontuações de corte validadas para o défice cognitivo ligeiro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 33 publications
2
34
0
7
Order By: Relevance
“…Concerning the second objective, the results of this study show that the only factor predicting the MMSE score was schooling. These results are in line with those found by Santana et al 58 where a significant positive correlation was found between MMSE and schooling (r = 0.24, p = 0.01). However, if we analyze the association between the variable with "cognitive / no cognitive impairment" and schooling, we can observe that people with over 11 years of schooling years have cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the second objective, the results of this study show that the only factor predicting the MMSE score was schooling. These results are in line with those found by Santana et al 58 where a significant positive correlation was found between MMSE and schooling (r = 0.24, p = 0.01). However, if we analyze the association between the variable with "cognitive / no cognitive impairment" and schooling, we can observe that people with over 11 years of schooling years have cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…However, in comparison to other widely used screening tests -like the Mini-Mental State Examination (MMSE) with a sensitivity level for MCI of 64.6%, and the MoCA test with a sensitivity level of 84.1% -the sensitivity values obtained for different ACE-III cut-off points are encouraging. 14,18 Future studies must determine whether the specificity values found in our study are due to the characteristics of our MCI sample or to the specifications of the instrument.…”
Section: Discussionmentioning
confidence: 92%
“…O Instituto Brasileiro de Geografia e Estatística (IBGE) realizou pesquisas censitárias para inferir na composição populacional e dar um pressuposto para uma política mais igualitária, sendo no ano de 2010, a atualização dos dados colhidos no ano 2000, onde se obteve inúmeros dados, inclusive sobre pessoas com deficiências [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionunclassified
“…Apresenta 9 itens que são pontuados de 0 a 2 pontos, totalizando 16 pontos, sendo o escore mais alto o melhor nível de equilíbrio e o menor, inversamente proporcional. C) Escala Mini Exame de Estado Mental 14,15,16 : é uma escala que faz a avaliação da cognição do participante. Possui 5 itens, podendo o participante, atingir até 5 pontos na orientação espacial, na orientação temporal e na atenção e cálculo; atingir no máximo 3 pontos na memória imediata e na memória de evocação e 9 pontos na linguagem, totalizando 30 pontos de pontuação máxima.…”
Section: Métodounclassified